2020
DOI: 10.1155/2020/6718495
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Mechanism of Traumatic Aortic Rupture (TAR)

Abstract: As many as 80% of patients with TAR die on the spot while out of those reaching a hospital, 30% would die within 24 hours. Thus, it is essential to better understand and prevent this injury. The exact mechanics of TAR are unknown. Although most researchers approve it as a common-sense deceleration injury, the exact detailed mechanism of TRA still remains unidentified. In this work, a deceleration mechanism of TAR was carried out using finite element analysis (FEA). The FE analysis aimed to predict inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…In agreement with previous study others showed that max stress occurs in the isthmus region. It was also concluded that comparing the stretching that occurs at the ascending aorta to the bending generated at the aortic arch, bending is a leading factor in BTAR 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with previous study others showed that max stress occurs in the isthmus region. It was also concluded that comparing the stretching that occurs at the ascending aorta to the bending generated at the aortic arch, bending is a leading factor in BTAR 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…While genetics and pharmacogenetics might not have direct application in cardiac surgery or interventional cardiology, personalized structural heart disease interventions, either surgical or percutaneous, include the consideration of predefined variables, thus enabling the precise tailoring of interventions to align with the special requirements and features of each patient [3][4][5]. This revolutionary shift has had a profound impact on the fields of interventional cardiology and cardiovascular surgery and especially the area of structural diseases, thus extending their capabilities and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy and similarity of the in silico Nuss procedure and actual surgery can be quantitatively elucidated through this process. On the other hand, in silico surgery simulation through FEA is extensively studied not only on the chest wall, but also on the spine, joints, blood vessels, and lungs, thus securing considerable reliability [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%